Chile's Rapid Growth in the 1990's-Good Policies, Good Luck, or Political Change? - Jadresic, Esteban; Zahler, Roberto (Washington, D.C. : International Monetary Fund, 2000)
Chile's average economic growth between 1990 and 1998 was above 7 percent per year, more than double than in previous decades, and higher than in any other Latin American country in the same period. This paper assesses empirically the main hypotheses suggested in the literature about the factors underlying this rapid growth: good economic policies, good luck in the external sector, and the country's return to a democratic system of government. The statistical and quantitative results indicate that Chile's rapid growth during the 1990s was due to good policies and the improved political situation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet